Learning Transfer in Initial Teacher Education: A Systematic Review of Evidence and Key Factors: Learning Transfer in Initial Teacher Education: A Systematic Review of Evidence and Key Factors - Henríquez, Juan Alejandro; Perines, Haylen; Sotomayor Soloaga, Pedro; Ordóñez-Jiménez, María Auxiliadora (Revista Complutense de Educación, 2026)
The transfer of learning from teacher education programmes to professional practice is a critical factor in improving educational quality. However, evidence on how this transfer occurs and which factors facilitate or hinder it remains fragmented. This study provides a systematic review of research on learning transfer in initial teacher education. A systematic search was conducted across Scopus, Web of Science, ERIC, and Dialnet, following PRISMA guidelines. After applying inclusion and exclusion criteria, 14 empirical studies were selected for analysis. The findings identify four key dimensions influencing learning transfer: the gap between university training and school contexts, the presence of facilitating factors (e.g., active learning and contextualized training), barriers that hinder transfer, and the role of key actors such as school-based mentors. The results highlight the need to strengthen practice-oriented approaches in teacher education and to provide structured opportunities for applying theoretical knowledge in real educational settings. This review contributes to the field by synthesizing current evidence and identifying key directions for improving the effectiveness of teacher education programmes.